Eulerian‐based virtual visual sensors to measure dynamic displacements of structures. Issue 10 (23rd December 2016) - Shariati, Ali; Schumacher, Thomas
Summary: Vibration measurements provide useful information about a structural system's dynamic characteristics and are used in many fields of science and engineering. Here, we present an alternative noncontact approach to measure dynamic displacements of structural systems using digital videos. The concept is that intensity measured at a pixel with a fixed (or Eulerian) coordinate in a digital video can be regarded as a virtual visual sensor. The pixels in the vicinity of the boundary of a vibrating structural element contain useful frequency information, which we have been able to demonstrate in earlier studies. Our ultimate goal, however, is to be able to compute dynamic displacements, i.e., actual displacement amplitudes in the time domain. In order to achieve that, we introduce the use of simple black‐and‐white targets that are mounted on locations of interest on the structure. By using these targets, intensity can be directly related to displacement, turning a video camera into a simple, computationally inexpensive, and accurate displacement sensor with notably low signal‐to‐noise ratio. We show that subpixel accuracy with levels comparable to computationally expensive block matching algorithms can be achieved using the proposed targets. Our methodology can be used for laboratory experiments, on real structures, and additionally, we see educational opportunities in K‐12 classroom. In this paper, we introduce the concept and theory of the proposed methodology, present and discuss a laboratory experiment to evaluate the accuracy of the proposed black‐and‐white targets, and discuss the results from a field test of an in‐service bridge.